Pengaruh Pengungkapan Islamic Social Reporting, Kinerja Indeks Maqashid Syariah, Pertumbuhan Perusahaan, Dan Ukuran Perusahaan Terhadap Nilai Perusahaan - Devega, Lidya; Fauzi, Nurul; Ihsan, Hidayatul; Rafi, Muhammad; Haslina, Welsi (Akuntansi dan Manajemen, 2025)
This research aims to examine and assess the influence of Islamic Social Reporting (ISR) disclosure, maqashid shariah index performance, company growth, and firm size on the firm value of Sharia Commercial Banks (BUS) listed under the Financial Services Authority (Otoritas Jasa Keuangan/OJK) throughout the 2019–2024 period. Employing a quantitative approach with purposive sampling, the study collected 35 observational data points from 7 BUS. The dependent variable, firm value, was measured using the Economic Value Added (EVA) indicator. Data were analyzed using multiple linear regression techniques with the Statistical Product and Service Solutions (SPSS) version 29 software. The findings reveal that, individually, ISR disclosure and maqashid shariah index performance significantly influence firm value, whereas company growth and firm size show no significant impact. Nonetheless, when examined simultaneously, ISR disclosure, maqashid shariah index performance, company growth, and firm size collectively exert a significant influence on firm value among Sharia Commercial Banks registered with the OJK.